Knowledge Management Practices in Small and Medium Enterprises: A Comparative Study - Lozano J. Azariah (International Journal of Innovative and Applied Finance, 2024)
This research investigates the knowledge management (KM) practices implemented in small and medium enterprises (SMEs) compared to larger organizations. Utilizing a mixed-methods approach, the study analyzes KM strategies, tools, and their impact on organizational performance. Results indicate that while SMEs face resource constraints, they often leverage informal networks and agile practices that can lead to effective knowledge management outcomes.